Understanding Accountability In Modern Organizations: A Non-Positivist Interpretation Of Accounting Practices - Adelia, Elza; Syarifuddin; Arifuddin (CITACONOMIA, 2025)
Accounting research has traditionally been grounded in positivist assumptions that treat accounting as a neutral and objective system for representing economic reality; however, such assumptions increasingly fail to capture the complex social, institutional, and political contexts in which accounting operates. This study examines accounting practices from a non-positivist perspective, conceptualizing accounting as a socially constructed and interpretive practice shaped by organizational discourse, power relations, and institutional pressures. Using an interpretive qualitative approach, data were collected through semi-structured interviews, document analysis, and non-participant observation to explore how organizational actors produce, interpret, and mobilize accounting information in everyday organizational settings. The findings demonstrate that accounting functions not merely as a technical mechanism but simultaneously as a tool for sensemaking, organizational control, and institutional legitimacy, actively constructing organizational reality by shaping meanings, guiding behavior, and reinforcing dominant narratives. By highlighting the symbolic, discursive, and disciplinary roles of accounting, this study contributes to interpretive and critical accounting literature and challenges the assumption of accounting neutrality, offering important implications for accounting research, practice, and policy in contemporary organizational contexts.